Embodied parallelism and immersion in virtual reality gaming. (April 2022) - Bollmer, Grant; Suddarth, Adam
This article argues that virtual reality produces a sense of immersion through embodied parallelism – a technical mediation in which the embodied gestures and movements of a player must correspond to what is represented within a VR game, a correspondence which relies on, but exceeds the visual and requires strange requirements for both player (in terms of their gestures and movements) and game (in terms of including particular limits that police the movements of the player's body). Attending to embodied parallelism refuses several longstanding assumptions about how virtual reality technologies, and media in general, generate the feeling of immersion – namely, the idea that immersion 'disembodies' in some way, or denies the existence of physical space beyond the boundary of a mediated simulation. Immersivity is premised on an explicit engagement with – and not exclusion of – both the physicality of the body and the physicality of a medium, if in deeply contradictory ways. As a case study to develop this concept, this article discusses the emerging virtual reality genre of 'physics games', games including, but not limited to, Blade & Sorcery, Boneworks and Half-Life: Alyx . These games take great lengths to simulate the physics of objects – they require simultaneously intrusive and yet 'natural' interfaces, in which the game demands the body to move as if it were manipulating objects that have a specific mass. Becoming 'good' at these games depends on the ability to discipline the body and conform to the demands of movement required by the simulation. Immersion, in this context, depends on a willingness to submit to these machinic, embodied demands, relying both explicitly on technical form but deliberately forgetting the materiality of gesture and mediation at the same time. This seeming contradiction, an engagement with both the materiality of gesture and the materiality of medium, is 'solved' through embodied parallelism and how it links player and game.